2016
DOI: 10.1128/jvi.02397-15
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Monoclonal Antibodies against a Cyclic Variant of Hepatitis C Virus E2 Epitope 412-422

Abstract: The hepatitis C virus (HCV) E2 envelope glycoprotein is crucial for virus entry into hepatocytes. A conserved region of E2 encompassing amino acids 412 to 423 (epitope I) and containing Trp420, a residue critical for virus entry, is recognized by several broadly neutralizing antibodies. Peptides embodying this epitope I sequence adopt a β-hairpin conformation when bound to neutralizing monoclonal antibodies (MAbs) AP33 and HCV1. We therefore generated new mouse MAbs that were able to bind to a cyclic peptide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Characterization of MAbs induced by C1 or C2 vaccination, via alanine scanning mutagenesis, affinity measurements, or crystallography, may yield information regarding the induced repertoire and possible molecular details underlying the observed difference between epitope I-specific binding and neutralization, for instance, MAb binding to portions of the epitope that are inaccessible in the context of E2 or the virion. Such characterization of C1 and C2-elicited MAbs, which was utilized recently for another cyclic epitope I design as noted above (45), could indicate the basis of neutralization in immunized sera from our constructs and inform second-generation designs of one or both of those antigens. Additionally, as glycosylation or mutation at N415 is associated with escape from HCV1 (25,51) and other MAbs (9), addition of a glycan at N415, in addition to N417, may induce antibodies capable of targeting this epitope with a binding footprint that does not include N415 while maintaining binding to the conserved residues L413 and W420.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Characterization of MAbs induced by C1 or C2 vaccination, via alanine scanning mutagenesis, affinity measurements, or crystallography, may yield information regarding the induced repertoire and possible molecular details underlying the observed difference between epitope I-specific binding and neutralization, for instance, MAb binding to portions of the epitope that are inaccessible in the context of E2 or the virion. Such characterization of C1 and C2-elicited MAbs, which was utilized recently for another cyclic epitope I design as noted above (45), could indicate the basis of neutralization in immunized sera from our constructs and inform second-generation designs of one or both of those antigens. Additionally, as glycosylation or mutation at N415 is associated with escape from HCV1 (25,51) and other MAbs (9), addition of a glycan at N415, in addition to N417, may induce antibodies capable of targeting this epitope with a binding footprint that does not include N415 while maintaining binding to the conserved residues L413 and W420.…”
Section: Discussionmentioning
confidence: 81%
“…The designs resulting from the metaserver methodology described in that study were larger and distinct from the cyclic designs we produced and tested in vivo. More recently, a study was reported featuring a cyclic epitope I construct with a different mode of disulfide cyclization than C1 or C2, including epitope residues 412 to 422 rather than 412 to 423 (C1) or 409 to 425 (C2) and no glycan at N417 (45). After mouse immunization with this antigen, several elicited MAbs were tested for epitope binding and neutralization, but no measurable neutralization was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Such alternate conformations appear to be critical for virus neutralization. A recent study by Sandomenico et al (52) showed that antibodies raised against cyclized AS412 peptides that adopt an alternative conformation were not neutralizing. From the present study, the CD81bs front layer resembles a highly flexible loop despite being held by two disulfide bonds and despite high sequence conservation, which is generally not associated with flexible loops in viral proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Rational vaccine design, in which select epitopes are emphasized, has so far had limited success for HCV. One approach relies on the induction of NAbs against extended or cyclic versions of linear epitopes (59)(60)(61). These approaches cannot readily be adapted to AR3A, as it has a conformational, nonlinear epitope.…”
Section: Fig 17mentioning
confidence: 99%